2022
DOI: 10.1111/evj.13566
|View full text |Cite
|
Sign up to set email alerts
|

Rib fractures in adult horses as a cause of poor performance; diagnosis, treatment and outcome in 73 horses

Abstract: Background: Rib fractures in adult horses are poorly documented.Objectives: To describe the presenting signs, diagnosis, treatment and outcome of horses diagnosed with rib fracture. Study design:Retrospective case series. Method:The clinical records and diagnostic images of all adult horses diagnosed with a rib fracture at three referral centres over a 15-year period were reviewed.Results: Seventy-three horses met the inclusion criteria. Horses presented due to either resistance to ridden work and poor perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 7 publications
0
18
0
1
Order By: Relevance
“…Only through increasing the understanding of associated risk factors can fractures be effectively diagnosed, hopefully at the prodromal stage, and longer‐term, can preventative measures be implemented to reduce injury rates on the racetrack. Hall et al 21 reported the unusual finding of rib fractures in 73 adult horses and identified the presenting clinical signs to commonly involve poor performance or resistance to ridden work; posing another differential that should be considered in the work up of these non‐specific clinical presentations.…”
Section: Care Of the Performance Horse With A Focus On Orthopaedicsmentioning
confidence: 99%
“…Only through increasing the understanding of associated risk factors can fractures be effectively diagnosed, hopefully at the prodromal stage, and longer‐term, can preventative measures be implemented to reduce injury rates on the racetrack. Hall et al 21 reported the unusual finding of rib fractures in 73 adult horses and identified the presenting clinical signs to commonly involve poor performance or resistance to ridden work; posing another differential that should be considered in the work up of these non‐specific clinical presentations.…”
Section: Care Of the Performance Horse With A Focus On Orthopaedicsmentioning
confidence: 99%
“…The aim of this retrospective case series by Suzy Hall and co‐workers in the UK was to describe the presenting signs , diagnosis , treatment and outcome of horses diagnosed with rib fracture .…”
Section: Rib Fractures In Adult Horsesmentioning
confidence: 99%
“…Poor performance was the owner's complaint in 56% (41/73) and lameness was reported in 64% (47/73) of the horses. The most common clinical sign observed in adult horses affected with rib fractures included pain on palpation of the fractured area in 38% (18/47) (Hall et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Palpation is a subjective technique and varies between horses and examiners, only 18/47 horses where palpation was recorded, showed signs of pain or discomfort. Swelling associated with the fracture site is not always noticeable (Hall,et al 2022). Ultrasound examination is often the preferred imaging technique used for diagnosis of rib fractures, especially in foals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation